Pemberdayaan Masyarakat Melalui Pengolahan Feses Ayam Menjadi Pupuk Organik yang Bernilai Ekonomis - Siti Yasya Ey Fathanah; Nudia Tuljannah; Kartini J; A. Rahmatia; Riskayanti; Afifah Nur Fadhilah; A. Agung Hariawan Patempoi (ITEKES Permata Ilmu Maros, 2026)
Chicken farming waste is one of the environmental problems commonly found in communities due to the increasing production of broiler chickens. Poorly managed chicken feces can cause unpleasant odors, increase fly populations, and pollute the environment around farming areas. However, chicken feces contain essential nutrients such as nitrogen (N), phosphorus (P), and potassium (K), making them potentially useful as economically valuable organic fertilizer. This community service activity aimed to improve community knowledge and skills in processing chicken feces into environmentally friendly and marketable organic fertilizer. The activity was conducted among livestock farmers and farmer groups in a village in Maros Regency through counseling, training, demonstrations, and mentoring on organic fertilizer processing using a simple fermentation technique with EM4. The results showed an increase in community understanding and skills in managing livestock waste into organic fertilizer. In addition to reducing environmental pollution, this activity also provided economic opportunities for the community through the utilization and marketing of organic fertilizer. Therefore, this community service activity contributed positively to community empowerment, environmental awareness, and the development of sustainable agriculture.